Perancangan Strategi Digital Marketing Bisnis pada UMKM Warung Jaka Tingkir - Alfiona Alfiona; Yuli Indah Fajar Dini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
In the 4.0 era, it is increasingly prevalent with the existence of new strategies in the business world or business, especially the food business, this strategy is Digital Marketing Strategic. Which strategy can make changes and new developments to the food business or business. Digital Marketing can help business owners or businesses to be able to reach a wider target market and also be able to carry out more efficient promotional targets. For this reason, the design and introduction of Digital Marketing is made so that the owner of this business or food business can develop his business more broadly and more efficiently. Which in this strategy makes various ways of promotion on social media. The object used as the location of devotion is Warung Jaka Tingkir. In this service, the author carried out various ways of promotion that had not previously been done by business owners such as creating Instagram along with feeds, creating location points on Google Maps and other promotional methods. The results obtained after digital marketing are the increasing insight and the increase in business income.